Shoulder external over internal rotation ratio is related to biomechanics in collegiate baseball pitching - Stokes, H. L.; Eaton, K.; Zheng, N. (Journal of Applied Biomechanics, 2024)
Altering baseball pitching mechanics affects both performance and the risk of injury. The purpose of this study is to investigate the relationships of shoulder external over internal rotation ratio (SEIR) and other shoulder rotational properties during physical exam and biomechanics of pitching for 177 collegiate baseball pitchers. The shoulder range of motion was quantitatively measured using a custom-made wireless device. Pitching motion data were collected at 240 Hz, and a custom program was created to calculate the throwing arm motion and loading during baseball pitching. Linear regression and analysis of variance tests were performed to investigate the relationships between the shoulder physical exam outcomes and throwing arm biomechanics. SEIR had significant correlations with shoulder horizontal adduction angle at foot contact, maximum shoulder external rotation angle, maximum shoulder linear velocity, and elbow angle at ball release. SEIR groups had significant differences in shoulder proximal force, adduction torque, internal rotation torque, and horizontal adduction torque, and in elbow medial force and varus torque. Glenohumeral internal rotation deficit and total rotational motion deficit had no relationships with throwing arm motions or joint loadings. Shoulder health should be monitored to improve understanding of pitching mechanics in collegiate baseball pitchers.